Chicks - San Jose Philip; Tagalog Ilang-Ilang Production, Inc., (Firm). (Manila Tagalog Ilang-Ilang)
We all have our own strategies to survive in this mysterious world. These three girls Salome, Bella, and Sylvia living in one apartment are earning their living through a so-called dirty job for women. But is it really the job or the intentions of the one doing these that contribute to its muddy wrappings? Chicks is a depiction of the real life survivors, the real friendships and the golden hearts though we see them covered with mud.
VCD
Directed by Philip San Jose
Rio Locsin, Lorna Tolentino, Amy Austria.
Keywords: Feature films